Is pulse oximeter a reliable tool for non‐critically ill patients with COVID‐19?. Issue 12 (21st October 2021) - Gürün Kaya, Aslıhan; Öz, Miraç; Akdemir Kalkan, İrem; Gülten, Ezgi; Çınar, Güle; Azap, Alpay; Kaya, Akın
Abstract: Introduction: Guidelines recommend using a pulse oximeter rather than arterial blood gas (ABG) for COVID‐19 patients. However, significant differences can be observed between oxygen saturation measured by pulse oximetry (SpO2 ) and arterial oxygen saturation (SaO2 ) in some clinical conditions. We aimed to assess the reliability of the pulse oximeter in patients with COVID‐19. Methods: We retrospectively reviewed ABG analyses and SpO2 levels measured simultaneously with ABG in patients hospitalised in COVID‐19 wards. Results: We categorised total 117 patients into two groups, in whom the difference between SpO2 and SaO2 was ≤4% (acceptable difference) and >4% (large difference). A large difference group exhibited higher neutrophil count, C‐reactive protein, ferritin, fibrinogen, D‐dimer and lower lymphocyte count. Multivariate analyses revealed that increased fibrinogen, increased ferritin and decreased lymphocyte count were independent risk factors for a large difference between SpO2 and SaO2 . The total study group demonstrated the negative bias of 4.02% with the limits of agreement of −9.22% to 1.17%. The bias became significantly higher in patients with higher ferritin, fibrinogen levels and lower lymphocyte count. Conclusion: Pulse oximeters may not be sufficient to assess actual oxygen saturation, especially in COVID‐19 patients with high ferritin and fibrinogen levels and low lymphocyte count with low SpO2 measurements.